Long-term monitoring of vegetation dynamics in the Goegap Nature Reserve, Namaqualand, South Africa - Van Rooyen, M.W. (Margaretha W.), 1950- (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2010.